Patient radiation dose in diagnostic cerebral angiography for intracranial aneurysm: local diagnostic reference levels from a single-center study in Thailand - Similan Pookplean; Phonlapat Meesa-nga; Sirikan Kittichotwarat; Petdao Petchuay (Radiation Protection Dosimetry, 2026)
Abstract Diagnostic cerebral angiography for intracranial aneurysms can deliver relatively high patient radiation doses, and locally derived diagnostic reference levels (DRLs) are important for optimization. This retrospective single-center study analyzed 186 procedures performed at Vajira Hospital between 2022 and 2024 using a biplane digital subtraction angiography system. Dose–area product (DAP), cumulative air kerma (CAK), fluoroscopy time, number of image frames, and number of three-dimensional rotational angiography (3DRA) acquisitions were recorded for each procedure. Median values across all years served as local typical dose values and were compared with published 75th percentile DRLs, consistent with the International Commission on Radiological Protection (ICRP) 135. The medians were 58.58 Gy·cm2 (DAP), 326.74 mGy (CAK), 6.41 min (fluoroscopy time), 525.50 frames, and 3.00 3DRA acquisitions, with no significant interannual differences. Typical values for DAP, CAK, and fluoroscopy time were lower than those reported in several national and international studies, indicating comparatively low patient doses.